Pengembangan Kecerdasan Emosional Siswa Melalui Program Kelas Tahfidz Di MTs Al Ghozaly Siwatu Wonosobo - Akimudin Akimudin; Ali Imron; Ngatoillah Linnaja (SPESIFIK: Jurnal Pendidikan dan Pembelajaran, 2024)
This research aims to: 1) to learn the concept of application of the tahfidz class program in an effort to develop the emotional intelligence of students of MTs Al Ghozaly Siwatu Wonosobo. 2) to know the implementation of the Emotional Intelligence of the student of MTs Al Gozaly Siwaatu Wnosobo through the Tahfidz Class program. 3) to learn about the results of emotional development of the students of the MTs. A type of qualitative research where research is field-based. Data collection techniques use participant observation methods, in-depth interviews, and documentation. Then the data sources are obtained from field research, qualitative research and case studies. Where data is obtained using the following data analysis processes: 1) Data reduction 2) Data analysis and 3) Conclusion or verification. The results show that: 1) Application of a tahfidz program at Al Ghozaly Siwatu Wonosobo MTs can improve student interest, concentration, and emotional intelligence by performing a variety of activities, such as completing learning, memorizing the Qur'an, and completing various tasks. 2) Self-care, emotional management, motivation, empathy, and building relationships are the focus of the program. 3) Students acquire enhanced emotional intelligency through a Tahfidz classroom program, like time management, empatics, and understanding other people's perspectives, which are important components in emotional development.